Biomechanical and Histomorphometric Characterization of the Melatonin Treatment Effect in the Carotid Artery Subjected to Hypobaric Hypoxia - Cerda-Villablanca, E; Garcia-Herrera, C; Rivera-Mancilla, E; Gordillo-Zavaleta, L; Navarrete-Rosales, A (Frontiers Media SA, 2025)
This study aims to assess the efficacy of melatonin in mitigating the adverse effects of hypobaric hypoxia on the cardiovascular system of neonatal lambs (30 days old). Two groups were considered for this purpose: (i) Melatonin-treated group (N = 5) and (ii) Control group (N = 6) without treatment. All subjects were exposed to hypobaric hypoxia during gestation and perinatal periods, with melatonin administered after birth. The study focused on the carotid artery, a known predictor of cardiovascular risk. Biomechanical tests, morphometric, and histological measurements were conducted, and a numerical model was developed based on the biomechanical data. Key findings showed remodeling effects: Firstly, a realignment of collagen fibers towards a longitudinal direction was observed with melatonin treatment, similar to non-hypoxic arteries. Second, changes in residual stress and ex-vivo luminal radius were noted, aiming to reduce wall stress and increase vascular resistance. These changes indicate an antihypertensive response, reducing the effects of increased blood pressure and flow due to hypobaric hypoxia. This study demonstrates that biomechanical and histomorphometric methodologies effectively assess the beneficial effects of melatonin treatment under hypobaric hypoxia exposure. © © 2025 Rivera, Navarrete, Garcia-Herrera, Gordillo, Cerda, Celentano, Gonzalez-Candia and Herrera.